Dynamic links between economic growth, institutions, fiscal policy and stock market development - Ghulam Rasool Madni (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
Economic growth is a most crucial factor that plays its role to improve the living standards in a country. But there is no consensus about the variables explaining the economic growth of economies. This paper is an attempt to explore the impact of institutional quality, instruments of fiscal policy, and stock market development on economic growth for a small developing economy, Pakistan over the time span of 1984-2016. To determine the long and short run relationship of the variables, Auto Regressive Distributed Lag (ARDL) bounds testing approach to integration is applied. An index of institutional quality is constructed by Principal Component Analysis (PCA) considering twelve institutional indicators given by International Country Risk Guide (ICRG). The findings of the study reveal a positive relationship of public spending, institutional quality and stock market development on economic growth of the country. It is suggested that improvement of institutional quality, productive public spending and efficient financial markets are driving forces for economic prosperity and development of Pakistan.